Quality Of Life of Laryngeal Carcinoma Patients after Total Laryngectomy - Achmad Prihadianto; Yussy Afriani Dewi; Agung Dinasti Permana (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Management of laryngeal carcinoma has been widely developed, either by surgery, radiotherapy, and/or chemotherapy. The treatment has a major impact on physical, social, and psychological health that can change the quality of life of patients. This study aimed to determine the quality of life of laryngeal carcinoma patients after total laryngectomy.Methods: This descriptive study was conducted from May to August 2018. Patients with post total laryngectomy at the Division of Ear, Nose, Throat, Head and Neck Surgery, Dr. Hasan Sadikin General Hospital, Bandung were recruited. Short Form 36 (SF-36) Study Questionnaire and the European Organization for Research and Treatment of Cancer Head and Neck Cancer Quality of Life Questionnaire (EORTC QLQ-H & N35) were used, and data were presented in the form of descriptive narratives and tables.Results: In total, 23 patients were included consisting of 19 men (82.61%) and women (17.39%), aged 56-65 years old. The mean score of quality of life in physical components of SF-36 was 87.55 ± 2.35 and in mental components was 85.35 ± 3.92. The highest score of quality of life of EORTC QLQ-H & N35 on the speech problem scale was 51.69 ± 6.36. Conclusion: The quality of life of laryngeal carcinoma patients after total laryngectomy is generally good, however, speech is the main problem and needs to be further elaborated to enhance the quality of life.